Vaccination and its social and behavioural drivers in children with disability in Fiji - Susan Woolfenden; Nadia Badawi; Sarah Mcintyre; Israt Jahan; Gulam Khandaker; Kristine Macartney; Margie Danchin; Hayley Smithers-Sheedy; Donald Wilson; William May; Meru Sheel; Ilisapeci Tuibeqa; et al. (BMJ Global Health)
Introduction Data on the vaccination of children with disabilities are limited across Pacific Island countries like Fiji. This study aimed to examine the vaccination status and measure the social and behavioural drivers influencing vaccination of children with disability in Fiji.Methods A cross-sectional survey was conducted in Suva–Nausori area, Rewa, Fiji among children with disabilities (eg, motor, vision, hearing, speech, intellectual, epilepsy) aged 2–19 years and their caregivers. Caregivers were interviewed using a questionnaire to collect data on sociodemographic, functional characteristics (UNICEF’s child-functioning tool), child’s vaccination status according to Fiji’s National Immunisation Programme (NIP), and drivers of vaccination using the WHO-UNICEF Behavioural and Social Drivers Tool. Descriptive and regression analyses were undertaken.Results In April–May 2023, 198 children and their caregivers were recruited from the study area. The mean age of participating children was 7.6 years, 67.7% were male. Of the 198 children, 55% were fully vaccinated against all vaccines provided under the NIP. Percentage vaccination was highest for dose 1 of each NIP vaccine antigen and declined for subsequent doses. Vaccination against all NIP vaccines was significantly lower among children aged 15–19 years, those with hearing difficulties, and whose caregivers had low confidence in vaccine safety, whereas vaccination was higher among children with mobility difficulties.Conclusion Study findings highlight the need for equitable access to vaccines for children with disability who are vulnerable to infection from vaccine-preventable diseases. Policies and response plans should emphasise inclusiveness and assist children with disabilities to overcome access barriers within existing vaccination programmes.